The Influence of Popularity, Credibility, and M-Banking Services on Customer Satisfaction and Loyalty at Bank BTN - Egy Zidan Pakhlevi; Raden Roro Ratna Roostika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of popularity, credibility, and the efficiency of Bank BTN's mobile banking services on customer satisfaction and loyalty. Utilizing a qualitative approach, data were collected through in-depth interviews with several customers. The findings indicate that both popularity and credibility play a significant role in shaping public interest in becoming customers, while the efficiency of digital services is a critical factor in determining satisfaction and loyalty levels. Recommendations are proposed to enhance digital promotion, improve the efficiency of mobile banking services, and expand product branding to better reach younger generations.